Integrating Due Process Into The Enforcement Framework of Criminal Law Politics - Laputigar, Rendy; Suhadi, Suhadi; Rodiyah, Rodiyah (Universitas Negeri Semarang (UNNES), 2024)
Criminal Law Reform endeavours to establish legal frameworks that meet society's evolving needs within the realm of criminal justice. It involves revising existing legal standards to craft new regulations that can effectively address contemporary challenges. The core aim is to keep pace with societal changes, ensuring that criminal law remains relevant and responsive to real-world circumstances. Central to this is the concept of due process, a cornerstone of criminal justice systems worldwide, which safeguards individual liberties and human rights. It underscores the intrinsic connection between criminal law and due process, highlighting their indispensable unity. This study explores the vital role of due process in shaping law enforcement practices within the criminal justice domain, seeking to assess its significance in upholding individual rights while facilitating efficient law enforcement. The research methodology involves qualitative analysis through the examination of legal texts, case studies, and evaluations of policies. Findings suggest that due process of law plays a vital role in balancing law enforcement effectiveness with civil liberties protection. The conclusion emphasizes the importance of integrating due process principles uniformly into criminal justice systems to promote fairness and strengthen the rule of law.